A climatological study of severe Heat Waves in India (MAUSAM, 1966)
Results of a climatological study of severe heat waves in India based on observations extending over a period of 51 years are presented, Their period of occurrence, frequency, intensity, persistency, extent, development and decay are discussed with the help of 4 diagrams and 7 tables.